Fourth-Generation Minimally Invasive Hallux Valgus Surgery With Guided Percutaneous System: Step-by-Step Surgical Technique - David Campillo-Recio, M.D., Ph.D.; Eduardo Quezada-Peralta, M.D.; Inés Farré-Galofré, M.D.; Juan-Antonio Calle-García, M.D.; Yeray Maldonado-Sotoca, M.D.; Oscar Peniche-Soto, M.D.; Glòria Albertí-Fitó, M.D., Ph.D. (Arthroscopy Techniques)
Hallux valgus is a common condition in foot and ankle surgery practice. Nonoperative treatment is the first line of management in painful cases. Once these actions have failed, surgical treatment is indicated. Minimally invasive surgery has gained popularity owing to its favorable clinical and radiologic outcomes. Nevertheless, the learning curve of these procedures may be difficult in the initial cases. To solve this problem, some guided devices have been developed. The objective of this technical note is to describe 3-dimensional hallux valgus deformity correction surgery through a guided percutaneous system.